Integration, disintegration and trade in Europe: Evolution of trade relations during the 1990s - Jarko Fidrmuc; Jan Fidrmuc (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2000)
The gravity model of trade is used to assess the economic consequences of new borders, which arose in the wake of break-ups of multinational federations in Eastern Europe. The intensity of trade relations among the constituent parts of Czechoslovakia, Soviet Union and the Baltics was very high around the time of disintegration, exceeding the normal level of trade approximately 40 times. Disintegration has been followed by a sharp fall in trade intensity. On the other hand, the trade liberalization between East and West has lead to gradual normalization of trade relations, and liberalization within CEFTA has reversed the fall in trade intensity among Central European countries.
Keywords: F13; F15; F41; 330; Gravity Model; International Trade; European Integration; Disintegration; Internationale Wirtschaftsbeziehungen; Wirtschaftsintegration; Gravitationsmodell; Schätzung; Europa